An Improved Min-Min Task Scheduling Algorithm with Grid Utilization and Minimized Makespan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Grid computing is hardware and software infrastructure which offers a economical, distributable, coordinated and credible access to strong computational abilities [1]. For optimal use of the abilities of large distributed systems, necessitate for successful and proficient scheduling algorithms is enforced. For diminution of total completion time and improvement of load balancing, many algorithms have been executed. In this paper, our goal is to propose new scheduling algorithm based on well known task scheduling algorithm i.e. Min-Min[1]. The proposed algorithm tries to use the advantages of this basic algorithm and excludes its drawbacks with better grid utilization and minimized makespan. In comparison to existing algorithms like Min-Min and improved Min-Min algorithm[1], our proposed algorithm is achieving better results for considered parameters.